Strategi Pemanfaatan Media Sosial (Tiktok dan Instagram) Untuk Personal Branding Wirausahawan Pemula - Hasyim, Hasyim; Ketia G, Gevy; Napitupulu, Dhaet Fretty; Siagian, Yeny Elfina (Journal of Education Transportation and Business, 2025)
This study aims to examine strategies for utilizing social media, specifically TikTok and Instagram, to build personal branding for aspiring entrepreneurs. The increasingly rapid development of the digital space demands that entrepreneurs build authentic, credible, and recognizable identities through visual and video platforms. The research method used a descriptive qualitative approach with a library study to analyze literature related to digital branding strategies. The results show that Instagram serves as a digital gallery emphasizing visual aesthetics and storytelling, while TikTok serves as a medium for accelerating visibility through trend-driven content and a powerful algorithm. Effective personal branding is formed through personal engagement, process transparency, and two-way communication with the audience. Furthermore, the ability to adapt to new platform features and algorithm literacy are crucial factors in increasing engagement and market reach. These findings confirm that aspiring entrepreneurs' personal branding is built through a combination of appropriate platform selection, identity authenticity, and strategic adaptation to social media dynamics.